Siblings of children with autistic spectrum disorders 2 - Siegel, Bryna (Henry Stewart Talks, 2012)
Sources of family stress, Sources of social support or stress, Family responses to community, Stressors from the immediate and greater world outside and their solution, Different kinds of stressors: personal, Marital, Child-rearing, Social support system, The role for psychotherapy, Different kinds of psychotherapy: Individual, Marital/dyadic, Family, Play therapy, Sibling groups, ASDs and proactive support, Sibling relationships, Risks for sub-optimal parenting, ASD and siblings solutions, Effect of ASD on parents and sibs, Understanding and preparing for the future